Physicochemical and Phytochemical Characterization of Orange Peel Flour (Citrus sinensis, Valencia Variety) - García Saavedra, Edgardo (2025)
This research aimed to characterize orange (Citrus sinensis) peel flour from the Valencia variety for its optimal use in the agro-industry. The study evaluated the physicochemical and phytochemical properties of orange peel flour subjected to drying temperatures of 60 °C and 70 °C, along with drying air velocities of 3 m/s and 5 m/s for each temperature. The drying process was conducted using a fluidized bed dryer. Statistical analysis revealed that the optimal temperature was 60 °C and the most suitable air velocity was 3 m/s for better preservation of physicochemical properties, specifically crude fiber (13.43%) and ash content (4.50%). Regarding phytochemical properties, the best results were achieved at 60 °C with a drying velocity of 5 m/s, yielding higher retention of polyphenols (782.52 ± 0.01 mg EAG/100 g) and antioxidant capacity (12.19 ± 0.28 DPPH/µmol ET/g of sample).